Degenerative Myelopathy in Hovawart Dogs: Molecular Characterization, Pathological Features and Accumulation of Mutant Superoxide Dismutase 1 Protein. (January 2021) - Mandrioli, Luciana; Gandini, Gualtiero; Gentilini, Fabio; Chiocchetti, Roberto; Turba, Maria E.; Avallone, Giancarlo; Pellegrino, Valeria; Menchetti, Marika; Kobatake, Yui; Kamishina, Hiroaki; Cantile, Carlo
Summary: Degenerative myelopathy (DM) is an adult-onset, progressive neurological disease affecting several breeds of dog. Homozygosity or compound heterozygosity for the canine superoxide dismutase 1 ( SOD1 ) gene mutations, possibly modulated by the modifier SP110 locus, are associated with a high risk for DM. Although the pathophysiological mechanisms are largely unknown, a role for mutant SOD1 in causing neuronal degeneration has been postulated. Three Hovawart dogs, 9–12 years of age, developed slowly progressive incoordination and weakness of the pelvic limbs leading to non-ambulatory flaccid paraparesis and muscle atrophy. Neuropathological lesions comprised axonal degeneration and loss of ascending and descending spinal pathways, which were most severe in the mid- to caudal thoracic segments. Accumulation of mutant SOD1 protein in neurons and reactive astrocytes was demonstrated by immunolabelling with the 16G9 antibody against the mutant SOD1 protein (p.E40K amino acid substitution). All three dogs were homozygous for the c.118A allele, but none had the SP110 'risk' haplotype, suggesting a weak association of SP110 with the onset of DM in this breed. Our data suggest that the Hovawart breed is predisposed to the SOD1:c.118G>A mutation, which is associated with the development of DM. Prevention of DM could be achieved with the help of strategies based on epidemiological and genetic testing.